The Arrangement of Dual Citizenship of the Indonesian Diaspora: A Legal and Human Rights Perspective - Made Nurmawati; I Nengah Suantra (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
Globalization has implications for the Indonesian diaspora in various parts of the world. Indonesian diaspora groups are aggressively fighting for their citizenship status in order to have dual citizenship. Law No. 12 of 2006 concerning Citizenship of the Republic of Indonesia has not regulated dual citizenship status for the Indonesian diaspora. The purpose of the study is to identify and analyze the dual citizenship position of the Indonesian diaspora in the Indonesian Citizenship Law. The research method used is normative legal research. The study suggested that citizenship status is very important because it relates to issues of rights and obligations. The bipartite status provides the protection and identity of the two countries. However, it is not the time to grant unlimited dual citizenship status because first, it needs an in-depth study of the implications of social, economic, cultural, political, security, and legal aspects as well as changes to the relevant related laws and regulations.